PWE-071 EndoRotor® use to manage walled-off pancreatic necrosis; first UK experience. Issue 2 (June 2019) - Morris, Liam; Geraghty, Joe; Makin, Alistair
Abstract : Introduction: 20% of patients with acute pancreatitis develop necrosis, which has a poor prognosis and significant mortality rate. Endoscopic necrosectomy is the primary intervention in the management of walled-off pancreatic necrosis (WOPN) 1 . After insertion of a lumen-apposing self-expanding metal stent (LASEMS), necrosis is removed using tools such as snares and forceps. Multiple procedures are often required, with repeated insertion of the endoscope into the cavity causing patient discomfort. EndoRotor® is a through-the-scope catheter with a rotating blade, cutting tissue which is then drawn into the catheter via suction. We present the first UK case series of EndoRotor® use for endoscopic necrosectomy. We aimed to evaluate the feasibility, safety and efficacy of its use in clearing WOPN. Methods: All procedures were performed under conscious sedation by endoscopists experienced in necrosectomy. A 54 year old female developed a 19 cm x 8 cm area of WOPN as a consequence of acute pancreatitis. A LASEMS was inserted and EndoRotor® necrosectomy was performed five days later. Most of the necrotic tissue was cleared and the procedure was well tolerated. Final clearance was completed with a further snare necrosectomy 6 days later. Imaging confirmed a significant reduction in the cavity size (8cm x 2cm) and the patient was discharged. A 56 year old female was admitted with acute pancreatitis and discharged home after 12 days. She was later admitted for elective cholecystectomy but became unwell. A CT found a 28cm x 9cm area of WOPN. A LASEMS was inserted and a necrosectomy was performed two days later. All visible necrosis was removed using EndoRotor® four days later. Later examination showed some residual necrosis within a well healing cavity, requiring no further intervention. A 48 year old male was admitted with acute severe pancreatitis, developing multiorgan failure requiring ICU care. A CT confirmed an 18cm x 12cm pancreatic collection and a LASEMS was inserted. The patient had four necrosectomies before having an EndoRotor® necrosectomy with good result. Two further necrosectomies were required before LASEMS removal. Results: All patients underwent EndoRotor® necrosectomy without complication. To achieve complete removal of WOPN the median number of procedures (including with EndoRotor®) was three (range 2–7). Conclusions: As EndoRotor® draws necrosis in by suction, repeated insertion of the endoscope into the cavity is not needed, allowing greater tolerability and improved clearance of necrosis. Initial experience suggests that EndoRotor® is a safe and efficient tool for clearing WOPN. Reference: Bakker OJ, et al. Dutch Pancreatitis Study Group. Endoscopic transgastric vs surgical necrosectomy for infected necrotizing pancreatitis: a randomized trial. JAMA . 2012;307(10):1053–61